Perbandingan Pendapatan Sistem Kemitraan Peternakan Ayam Broiler di Kota Pekanbaru. - Cepriadi Cepriadi (Universitas Bengkulu, 2010)
ABSTRACTThis research was done at PT. Ramah Tamah Indah in Pekanbaru City, this research aim to know companies system and concept of partnership, implementation conception of partnership, and knowing comparison mount the breeder earnings. This research was done during eight month, from Sept to November 2009. Technique of intake sampel is method of purposive sampling where breeder taken as responder is breeder with the scale criterion of effort ? 10.000 tail of chicken broiler. From entire/all breeder population taken 5 breeder which have partner with the division system of result of pursuant to Index Produce (IP) and 5 breeder which have partner with the system of sharing holder 50:50. The result show the partnership concept that could be realized are conservancy fee range, medium produce the livestock provided by a company, gift insentive, technical aid from the company, marketing guarantee, and election of system of result division agreed on by both parties. Average of net earning of effort livestock of chicken of broiler system of index production (IP) is Rp 5.891.662,- and for the system of sharing holder 50:50 is Rp 8.466.241,-. And seen from result the T test obtained conclusion that at this period, earnings of breeder of system of sharing holder 50:50 bigger than system breeder of index production (IP)Keywords: broiler’s farm, partnership, income, two kinds of partner pattern